Beneficial interaction between rice stunt virus and its insect vector Nilaparvata lugens Stal based on life table - LISTIHANI LISTIHANI; I GUSTI AYU DIAH YUNITI; PUTU EKA PASMIDI ARIATI; NI PUTU PANDAWANI; DEWA GEDE WIRYANGGA SELANGGA; I GEDE RAI MAYA TEMAJA; GUSTI NGURAH ALIT SUSANTA WIRYA; I PUTU SUDIARTA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Listihani L, Yuniti IGAD, Ariati PEP, Pandawani NP, Selangga DGW, Temaja IGRM, Wirya GNAS, Sudiarta IP. 2023. Beneficial interaction between rice stunt virus and its insect vector Nilaparvata lugens Stal based on life table. Biodiversitas 24: 4690-4698. The brown planthopper (Nilaparvata lugens) causes direct and indirect damage as a stunting virus vector in rice. Insect vectors and viruses are closely related with respect to disease transmission to host plants. Thus, this research aimed to determine the specific relationship between a virus and its insect vector on the biology and demography statistics of viruliferous brown planthopper (BPH). Research method included the propagation of N. lugens and stunt virus inoculum, the observation of cohort, stadia duration and egg survival rates, imago life span, and N. lugens life table. The BPH life table was arranged with the jackknife method for two treatments: plants infected by stunt virus and healthy plants. The research result showed that plants infected by stunt virus can shorten the BPH nymphal development stage from instar 2 to instar 5, life cycle, preoviposition period, and double time. Plants infected by stunt virus did not influence the BPH hatching pattern but influenced the total number of hatching eggs. The next BPH generation of stunt virus inflected plants increased 29.51 times more from the previous generation, while on healthy plants, the next BPH generation only increased 27.51 times. Virus-infected plants generally appeared to be superior quality hosts for vectors compared to uninfected plants, thus enhancing vector life table and virus spread.